Isotope Fractionation of Toluene: A Perspective to Characterise Microbial In Situ Degradation - Richnow, H.H. (ScientificWorldJournal, 2002)
A concept to assess in situ biodegradation of organic contaminants in aquifers is presented. The alteration of the carbon isotope composition of contaminants along the groundwater flow path indicates microbial degradation processes and can be used as an indicator for in situ biodegradation. The Rayleigh equation was applied to calculate the percentage of the in situ biodegradation (B[%]) using the change in the isotopic composition of contaminants (R(t)/R(0)) along the ground water flow path and a kinetic carbon isotope fractionation factor (αC) derived from defined biodegradation experiments in the laboratory. When the groundwater hydrology is known and a representative source concentration (C(0)) for a groundwater flow path can be determined, the extent of in situ biodegradation can be quantified.